Does implied community size predict likeability of a similar stranger? - Launay, J; Dunbar, R (Elsevier, 2015)
Homophily, the tendency for people to cluster with similar others, has primarily been studied in terms of proximal, psychological causes, such as a tendency to have positive associations with people who share traits with us. Here we investigate whether homophily could be correlated with perceived group membership, given that sharing traits with other people might signify membership of a specific community. In order to investigate this, we tested whether the amount of homophily that occurs between strangers is dependent on the number of people they believe share the common trait (i.e. the size of group that the trait identifies). In two experiments, we show that more exclusive (smaller) groups evoke more positive ratings of the likeability of a stranger. When groups appear to be too inclusive (i.e. large) homophily no longer occurs, suggesting that it is not only positive associations with a trait that cause homophily, but a sense of the exclusiveness of a group is also important. These results suggest that group membership based on a variety of traits can encourage cohesion between people from diverse backgrounds, and may be a useful tool in overcoming differences between groups.